2021
DOI: 10.1364/boe.443477
|View full text |Cite
|
Sign up to set email alerts
|

Study of cerebrovascular reactivity to hypercapnia by imaging photoplethysmography to develop a method for intraoperative assessment of the brain functional reserve

Abstract: Intraoperative assessment of cerebrovascular reactivity is a relevant problem of neurosurgery. To assess the functional reserve of cerebral blood flow, we suggest using imaging photoplethysmography for measuring changes in cortical perfusion caused by CO2 inhalation. Feasibility of the technique was demonstrated in three groups of anesthetized rats (n=21) with opened and closed cranial windows. Our study for the first time revealed that the hemodynamic response to hypercapnia strongly depends on the cranial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In a simplified sense, a decrease in the tone of the vascular wall should be accompanied by an increase in APC, whereas an increase in tone should lead to a decrease in APC 53 . The results of studies carried out by our group using both unconditional vasodilating agents, such as CO 2 41 or the carbonic anhydrase inhibitor dorzolamide 40 , and neurogenic dural vasodilation 42 fully confirm such a performance.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In a simplified sense, a decrease in the tone of the vascular wall should be accompanied by an increase in APC, whereas an increase in tone should lead to a decrease in APC 53 . The results of studies carried out by our group using both unconditional vasodilating agents, such as CO 2 41 or the carbonic anhydrase inhibitor dorzolamide 40 , and neurogenic dural vasodilation 42 fully confirm such a performance.…”
Section: Discussionmentioning
confidence: 64%
“…We have recently shown that a multimodal approach using imaging photoplethysmography (iPPG) at green illumination synchronized with the electrocardiogram (ECG) can serve as a reliable tool for studying intracranial blood flow in rats under various experimental conditions 39 41 . In particular, we identified new optical markers of trigeminal afferents activation and determined their sensitivity 42 to valproic acid and sumatriptan, two clinically effective drugs for preventive and abortive migraine treatment, respectively 43 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the method of imaging PPG (iPPG) has recently become increasingly used to estimate tissue perfusion in vivo, allowing for the quantification of the spatial distribution of the blood flow parameters [ 28 , 29 ]. Moreover, it was recently shown that iPPG allows for the assessment of the local distribution of arterial vascular tone [ 30 ], as well as vascular resistance [ 31 ].…”
Section: Introductionmentioning
confidence: 99%